Artificial intelligence versus expert: a comparison of rapid visual inferior vena cava collapsibility assessment between POCUS experts and a deep learning algorithm. Issue 5 (31st July 2020) - Blaivas, Michael; Adhikari, Srikar; Savitsky, Eric A.; Blaivas, Laura N.; Liu, Yiju T.
Abstract: Objectives: We sought to create a deep learning algorithm to determine the degree of inferior vena cava (IVC) collapsibility in critically ill patients to enable novice point‐of‐care ultrasound (POCUS) providers. Methods: We used publicly available long short term memory (LSTM) deep learning basic architecture that can track temporal changes and relationships in real‐time video, to create an algorithm for ultrasound video analysis. The algorithm was trained on public domain IVC ultrasound videos to improve its ability to recognize changes in varied ultrasound video. A total of 220 IVC videos were used, 10% of the data was randomly used for cross correlation during training. Data were augmented through video rotation and manipulation to multiply effective training data quantity. After training, the algorithm was tested on the 50 new IVC ultrasound video obtained from public domain sources and not part of the data set used in training or cross validation. Fleiss' κ was calculated to compare level of agreement between the 3 POCUS experts and between deep learning algorithm and POCUS experts. Results: There was very substantial agreement between the 3 POCUS experts with κ = 0.65 (95% CI = 0.49–0.81). Agreement between experts and algorithm was moderate with κ = 0.45 (95% CI = 0.33–0.56). Conclusions: Our algorithm showed good agreement with POCUS experts in visually estimating degree of IVC collapsibility that has been shown in previously published studies to differentiate fluid responsive from fluid unresponsive septic shock patients. Such an algorithm could be adopted to run in real‐time on any ultrasound machine with a video output, easing the burden on novice POCUS users by limiting their task to obtaining and maintaining a sagittal proximal IVC view and allowing the artificial intelligence make real‐time determinations.